A STUDY ON FACTORS RESTRICTING PURCHASE OF GREEN PRODUCTS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In spite of consumers’ awareness and  consciousness regarding environmental issues,  there is a lack of purchase of green products  by consumers. They are showing concern for  environment; but they are not purchasing  green products. There are various factors which  negatively affect the purchase of green products  by consumers. So this study was conducted with  an objective to explore the factors restricting  rural consumers to buy green FMCG products.  For this purpose data were collected from 200  respondents. By applying factor analysis; ten  factors were explored regarding restricting the  rural consumers to buy green FMCG products.  These factors include Lack of knowledge and  promotion; Uncaring Behaviour; Inefficacy  of green products; Negative attitude and  speciousness regarding advertisements claims;  Negligence towards green products; Ambiguity  in claims and cost factor; lack of promotional  incentives and quality; Self-inefficacy and lack  of belief; Ineffective labeling and Complex  exercise.
Keywords: green products; environmental issues; FMCG products; Inefficacy of green products and speciousness regarding advertisements claims